Extremism: a philosophical analysis - Cassam, Quassim (Routledge, Taylor & Francis Group, 2022)
Extremism is one of the most charged and controversial issues of the 21st Century. Despite myriad programs of deradicalization and prevention around the world, it remains an intractable and poorly understood problem. Yet it can also be regarded as a positive force - according to Martin Luther King Jnr., "the question is not whether we will be extremists, but what kind of extremists we will be." In this much-needed and lucid book, Quassim Cassam identifies three types of extremism--ideological; methods; and mindset extremism--and uses them to discuss the following fundamental topics and issues: What is extremism? What are the methods adopted by extremists? Is there an extremist 'mindset' and if so, what is it? What role do ideas of purity, victimhood and humiliation play in understanding extremism? How does extremism differ from fanaticism and fundamentalism? How does one become an extremist and how should we understand deradicalization? Throughout the book, Quassim Cassam uses many compelling examples, ranging from the Khmer Rouge, the IRA, Al-Qaeda, and Timothy McVeigh to Philip Roth's novel American Pastoral and counter-extremism programs, including the UK's 'Prevent' strategy. Clear-headed and engaging, Extremism: A Philosophical Analysis is essential reading for anyone interested in this important topic, not only in Philosophy but related disciplines such as Politics and International Relations, Conflict and Terrorism studies, Law, Education and Religion. It will also be of great interest to policy makers and those engaged in understanding extremism at any level.